Konsep Gadai Syariah Menurut Syafi’i Antonio - Dewi Kumala Sari Hasibuan; Pani Akhiruddin Siregar (Jurnal Penelitian Medan Agama, 2020)
This research aims to find out the concept of sharia pawn according to Syafi’i Antonio and the utilization of sharia pawnshop according to Syafi’i Antonio. Sharia pawn is sharia gold pawn. Qualitative research method is sourced in primary data in the form of library research that examines the Concept of Sharia Pawn according to Syafi’i Antonio by reviewing his book titled “Sharia Bank: From Theory to Practice”. As for the results of research: (1) The concept of sharia pawn according to Syafi’i Antonio is more to the application in sharia banking because ar-rahn or pawn contract is used in sharia banking as a complementary product; and (2) The utilization of sharia pawn according to Syafi’i Antonio which can be taken from the principle of ar-rahn is to maintain the possibility of customers to default on the financing facilities provided by the bank; provide security for all savers and depositholders that the funds will not disappear if the borrower's customer is unable to promise because there is an asset or goods (marhun) held by the bank; and if rahn is applied in the pawnshop mechanism, then of course the goods will be very helpful to our brothers who have difficulty funding especially in those areas.